2003
DOI: 10.1002/ceat.200306101
|View full text |Cite
|
Sign up to set email alerts
|

The Droplet Population Balance Model – Estimation of Breakage and Coalescence

Abstract: A droplet population balance model is employed in order to describe the hydrodynamic behavior of solvent extraction columns. This model describes the axial change of local column holdup and local droplet size distributions due to the basic phenomena, like droplet rising, axial dispersion, droplet breakage and coalescence. In order to reduce experimental efforts, single and swarm droplet experiments in small lab-scale devices were performed. For this, a rotating disc contactor (RDC) with one compartment and a V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…According to Simon et al (2003) the breakup of droplets in turbulent flow is referred to four mechanisms.…”
Section: Breakup Kineticsmentioning
confidence: 99%
“…According to Simon et al (2003) the breakup of droplets in turbulent flow is referred to four mechanisms.…”
Section: Breakup Kineticsmentioning
confidence: 99%
“…For a Kühni and a RDC extraction column the published standard hydrodynamic relationships for axial dispersion of both of the phases and the slip velocity have been used so far. The breakage of the droplets was calculated on the basis of a modified We-number by Cauwenberg et al [14] adapted to the specific column geometry by Modes [12] and Simon et al [15,25]. A new attempt was made to assess the droplet swarm hydrodynamics of this two stirred extraction columns on coalescence models based on the film drainage for undeformable and deformable drops with partially mobile interfaces, using the lubrication approximation of Chesters [8].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is no general correlation to predict the coalescence rate. However, basic experiments in a Venturi-tube have shown that the coalescence probability of droplets strongly depends on the droplet size, the hold-up and system properties [68][69][70]. Therefore, it is not possible to introduce a correlation for predicting the droplet coalescence independent of solving the population balance equation describing this phenomenon.…”
Section: Coalescence Parameters Estimation Pac-kagementioning
confidence: 99%